Plant cryopreservation: Principles, applications, and challenges of banking plant diversity at ultralow temperatures - Nagel, Manuela; Pence, Valerie; Ballesteros, Daniel; Lambardi, Maurizio; Popova, Elena; Panis, Bart (Annual Reviews, 2024)
Progressive loss of plant diversity requires the protection of wild and agri-/horticultural species. For species whose seeds are extremely short-lived, or rarely or never produce seeds, or whose genetic makeup must be preserved, cryopreservation offers the only possibility for long-term conservation. At temperatures below freezing, most vegetative plant tissues suffer severe damage from ice crystal formation and require protection. In this review, we describe how increasing the concentration of cellular solutes by air drying or adding cryoprotectants, together with rapid cooling, results in a vitrified, highly viscous state in which cells can remain viable and be stored. On this basis, a range of dormant bud–freezing, slow-cooling, and (droplet-)vitrification protocols have been developed, but few are used to cryobank important agricultural/horticultural/timber and threatened species. To improve cryopreservation efficiency, the effects of cryoprotectants and molecular processes need to be understood and the costs for cryobanking reduced. However, overall, the long-term costs of cryopreservation are low, while the benefits are huge. Expected final online publication date for the Annual Review of Plant Biology, Volume 75 is May 2024. Please see http://www.annualreviews.org/page/journal/pubdates for revised estimates.